Cover crops in no-tillage crop rotations in eastern and western Kansas - Arnet, Kevin Broc (Kansas State University, 2010)
Replacing fallow periods with cover crops can provide many benefits including soil quality improvements and reduced nitrogen fertilizer requirements. Field experiments were established near Garden City, KS with winter wheat and fallow phases as main plots, thirteen legume or non-legume cover crops, continuous winter wheat, and fallow as subplots, and cover crop termination method as sub-subplots. Treatments containing triticale had greatest water use efficiency (19.9 kg ha[superscript]-1 mm[superscript]-1) and aboveground biomass (3550 kg ha[superscript]-1), but subsequent winter wheat yields were reduced due to a reduction in volumetric water content. Increased soil residue through greater cover crop biomass resulted in increased precipitation storage efficiency during the fallow period, but water requirements to produce biomass depleted soil moisture more than growing a low biomass crop or fallow. In years of above-average precipitation, low biomass cover crops might be grown with little to no negative effect on subsequent wheat yields. A second field experiment was established near Manhattan, KS with fallow, double crop soybean, and four cover crop treatments planted after wheat harvest in a winter wheat-grain sorghum-soybean no-till cropping system, with five nitrogen treatments applied to the sorghum crop to estimate nitrogen contribution of the cover crops. Greatest above ground biomass production and nitrogen accumulation was observed with sorghum-sudan grass. At the 0 kg ha[superscript]-1 N rate, grain sorghum yields were reduced 1200 kg ha[superscript]-1 following sorghum-sudan grass, while all other cover crop treatments provided a 20-30 kg ha[superscript]-1 N equivalent benefit. Sorghum yields might be reduced following large biomass producing cover crops when nitrogen is limiting, but a small nitrogen benefit might be realized following low C:N ratio cover crops. Cover crop productivity and their subsequent effects on grain sorghum performance were evaluated in field studies established near Manhattan and Hutchinson, KS in 2008 and 2009. Sixteen summer or fall cover crop species were planted in no-tillage winter wheat stubble and evaluated for biomass production, nitrogen concentration, and nitrogen accumulation. Summer annual grass species produced the greatest biomass, 3392 kg ha[superscript]-1 and greater, and legume species accumulated the greatest amounts of nitrogen, averaging 43 kg ha[superscript]-1. Grain sorghum yields were 867 kg ha[superscript]-1 greater following summer cover crops compared to fall cover crops. Cover crops had a significant effect on sorghum performance, with yields 1240 kg ha[superscript]-1 greater following legume cover crops.
Keywords: No-tillage; Cover crop; Water use; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)